Correction of Astigmatism by a Single-Focus Toric Intraocular Lens during Cataract Surgery: Refractive State and Visual Acuity - M.A. Alnoelaty Almasri; V. C. Stebnev (Oftalʹmologiâ)
Purpose: the main purpose of study is to obtain a better visual outcome after implantation of a monofocal toric IOLs by accurate measurement, calculations and visual assessment.Methods. Fifty eyes with astigmatism of more than 2.5 D were included in a hospital-based prospective study. A biometric evaluation is done by Lenstar. Barette's toric calculation method is used to measure toric IOLs power. In a vertical position, preoperative axis marking was done by both bubble marker and direct slit beam. On table, in a horizontal position, axis marking was reassessed. After phacoemulsification, a monofocal Supra Phob toric IOL was implanted and rotated to match corneal axis marking. Best-corrected visual acuity was measured postoperatively at 1 and 3 months.Results. Reduction of mean of refractive astigmatism was reported postoperatively from 4.0 ± 0.79 preoperatively to 0.7 ± 0.28 at 1 month and 0.6 ± 0.27 at 3 months postoperatively. In whole, 96 % has residual astigmatism less than 1 D at 3 months postoperatively, while 8 % eyes had residual astigmatism more than 1 D. In whole, 76 % patients had IOLs rotation of less than or equal to 5°, 20 % patients had it between 6° and 10° and 4 % eyes had more than 10° at day 7 postoperatively, in which repositioning of IOLs was required.Conclusion. To reduce postoperative residual astigmatism after toric IOLs and to get better results, accurate measurement of parameters and proper calculation are essential.